Mathematical and computer modeling of seismic processes based on a soliton approach - Бомба, Андрій Ярославович; Турбал, Юрій Васильович; Турбал, Маріанна Юріївна; Радовенюк, Олена Віталіївна (Technology audit and production reserves, 2015)
In this paper we consider a mathematical model of seismic process, taking into account the role of solitary waves as a shocks "trigger". Methods of forecasting are based on evaluating trajectories of individual solitons and clarification of shocks probability. We allocate among the entire set of shocks individual subsets caused by the same soliton and construct of hypothetical trajectory of the solitons. The probability of a shock can be verified taking into account the soliton components of seismic process. The information system for the analysis of soliton component seismic processes was developed. We show the effectiveness of soliton approach and the possibility of its application to the analysis of seismic processes in several regions of the Earth by using this information system.